The Plot Thickens: Haploid and Triploid-Like Thalli, Hybridization, and Biased Mating Type Ratios in Letharia - Ament-Velásquez, Sandra Lorena; Tuovinen, Veera; Bergström, Linnea; Spribille, Toby; Vanderpool, Dan; Nascimbene, Juri; Yamamoto, Yoshikazu; Thor, Göran; Johannesson, Hanna (Frontiers in Fungal Biology, 2021)
The study of the reproductive biology of lichen fungal symbionts has been traditionally challenging due to their complex lifestyles. Against the common belief of haploidy, a recent genomic study found a triploid-like signal in Letharia. Here, we infer the genome organization and reproduction in Letharia by analyzing genomic data from a pure culture and from thalli, and performing a PCR survey of the MAT locus in natural populations. We found that the read count variation in the four Letharia specimens, including the pure culture derived from a single sexual spore of L. lupina, is consistent with haploidy. By contrast, the L. lupina read counts from a thallus' metagenome are triploid-like. Characterization of the mating-type locus revealed a conserved heterothallic configuration across the genus, along with auxiliary genes that we identified. We found that the mating-type distributions are balanced in North America for L. vulpina and L. lupina, suggesting widespread sexual reproduction, but highly skewed in Europe for L. vulpina, consistent with predominant asexuality. Taken together, we propose that Letharia fungi are heterothallic and typically haploid, and provide evidence that triploid-like individuals are hybrids between L. lupina and an unknown Letharia lineage, reconciling classic systematic and genetic studies with recent genomic observations.